Analysis of Educational Environment at Al-Azhar Mariuk Vocational School, Tambakdahan District - Adam Hasyim; Undang Ruslan Wahyudin (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2023)
Improving the Quality of Education at Al-Azhar Mariuk Vocational School, Tambakdahan District is the new title of this research. The nature of this type of research is a qualitative case study. The purpose of this research is to improve the standard of formal education held by SMK Al-Azhar Mariuk, Tambakdahan District. Information collected through interviews, documentation, and perceptions. Covers all aspects of the school environment, from the deputy head to TU staff, in carrying out the task of developing a vision, mission and goals, compiling an organizational structure, compiling work plans, compiling school directives, and creating a vital administrative data framework for Madrasahs. The duties of the madrasa head cannot be separated from school regulations. Human resources who are skilled in their fields, education and learning programs, as well as students who have graduated show the quality of Madrasah Diniyah Al-Azhar. the progress achieved by the head of the madrasa in improving the quality of Madrasah Diniyah Al-Azhar in terms of human resources and learning strategies.